ERRORS IN WRITING RECOUNT TEXT MADE BY THE EIGHTH GRADE STUDENTS OF SMP N 2 NGEMPLAK BOYOLALI IN 2015/2016 ACADEMIC YEAR - Prasetyowati, Yunia Dwi (JoLLIET, 2016)
This study was aimed to identify the types of errors made by the eighthgrade students of SMP N 2 Ngemplak Boyolali in writing recount text,especially to identify the types of lexical, syntactical, and discourse errors,and to find out the frequency of each type of errors, dominant type of errors,and the sources of errors. The type of this research was descriptivequalitative research. In collecting the data, the writer used elicitation. Itconsisted of four steps; the writer gave explanation about recount text,askedthe students to make recount text with the topic given, read and marked thetypes of errors in the students writing composition, wrote the erroneoussentences and classified all types of error based on linguistic category andsurface strategy taxonomy. The technique for analyzing data wereidentification of errors, classifying into error types, describing the frequencyof error, describing the dominant type of error, analysis of the sources oferror and describing the purposed remedial teaching. The result of the studyshowed that lexical errors was 15,51 % consisting of False friend (similar inmeaning), False friend (similar in form), Wrong spelling, and Codeswitching. Syntactical errors was 79,08 %, consisting of Verb (addition ofverb, misuse of verb in past tense, addition of to in present tense), Noun(omission of âs in plural marker, omission of possessive adjective, additionof âs in plural marker), BE (omission of BE, addition of BE in past tense,misuse of BE), Pronoun (omission of âs in possessive pronoun ), Phrase(misordering noun phrase), Article (omission of article the, omission ofarticle a , addition of article the), Preposition (omission of preposition,addition of preposition, misuse of preposition ), Conjuction (omission ofconjuction), Sentence Construction (omission had as predicate, omission ofsubject). Discourse errors was 5,36 %, consisting of generic structure andconjuction. The dominant type of errors was the misuse of verb in past tense.The writer also found two sources of errors, namely Interlingual transfer andIntralingual transfer.Key words: Error Analysis, Linguistic Category Taxonomy, RecountText, Surface Strategy Taxonomy